Juridical analysis of termination of employment due to the Covid-19 pandemic In the context of Indonesian employment law and citizenship education - Kurniawan, Itok Dwi; Septiningsih, Ismawati; Santos, Jose Gama (Universitas Negeri Yogyakarta, 2023)
The Indonesian government has declared Covid-19 a pandemic, leading to restrictions such as working from home and room capacity limits. These restrictions have resulted in numerous layoffs, and the pandemic has been deemed a national disaster, with laws and regulations like Presidential Decree No. 12 of 2020 strengthening the reasons for entrepreneurs to consider it a force majeure event. The economic sector's decline has direct implications for employees, both in formal and informal sectors, due to decreased production, depletion of industrial raw materials, weakening of the Rupiah against the Dollar, decline in Indonesian tourism, and the fall of the composite stock index. Employers have been forced to lay off their workers. Legal protection for workers includes termination of employment (PHK) and layoff provisions regulated by Articles 150-172 of Law 13/2003. This descriptive analysis aims to provide an overview of legal protection for workers during the pandemic, including the analysis and interpretation of laws and regulations related to the problem under study.